Occupation-specific suicide risk in England: 2011–2015. (October 2019) - Windsor-Shellard, Ben; Gunnell, David
Abstract : Background: Previous research has documented marked occupational differences in suicide risk, but these estimates are 10 years old and based on potentially biased risk assessments. Aims: To investigate occupation-specific suicide mortality in England, 2011–2015. Method: Estimation of indirectly standardised mortality rates for occupations/occupational groups based on national data. Results: Among males the highest risks were seen in low-skilled occupations, particularly construction workers (standardised mortality ratio [SMR] 369, 95% CI 333–409); low-skilled workers comprised 17% (1784/10 688) of all male suicides (SMR 144, 95% CI 137–151). High risks were also seen among skilled trade occupations (SMR 135 95% CI 130–139; 29% of male suicides). There was no evidence of increased risk among some occupations previously causing concern: male healthcare professionals and farmers. Among females the highest risks were seen in artists (SMR 399, 95% CI 244–616) and bar staff (SMR 182, 95% CI 123–260); nurses also had an increased risk (SMR 123, 95% CI 104–145). People in creative occupations and the entertainment industry – artists (both genders), musicians (males) and actors (males) – were at increased risk, although the absolute numbers of deaths in these occupations were low. In males (SMR 192, 95% CI 165–221) and females (SMR 170, 95% CI 149–194), care workers were at increased risk and had a considerable number of suicide deaths. Conclusions: Specific contributors to suicide in high-risk occupations should be identified and measures – such as workplace-based interventions – put in place to mitigate this risk. The construction industry seems to be an important target for preventive interventions. Declaration of interest: None.